Sudden workshops as a didactic strategy for the development of creativity in the initial processes of teaching architecture - Salazar-Ceciliano, Enmanuel (2020)
Creativity is one of the most recognized skills of architects, therefore, its development is one of the main challenges during the learning process. Theories like those comparing the creative process to a black box have been supported for decades. In this, the designer obtains satisfactory results but is not able to base the inputs that led him to the final object or to replicate the steps in another project. On the contrary, another method that defines creativity as a glass box has emerged, where there is rigorous prior research that allows the designer to fill himself with resources and variables to start his projectual process. Starting from this approach, it is common to see students, mainly those in the first year, overwhelmed by the blank paper and various factors that they still cannot interpret or relate. Therefore, this document presents a methodology that implements sudden workshops, or quick exercises in class, as a tool for students to make design decisions supported on their previous research and start their creative process. The proposal is based on the experience carried out in the Laboratory of Architecture II of the Architecture and Urbanism School of the Costa Rica Institute of Technology during the second semester of 2019.